Serum Inflammatory and Oxidative Biomarkers as Predictors of Severity and Clinical Outcomes in Ischemic Heart Disease. A Cross-Sectional Clinical Study - Muhammad Hussain, Aamir Siddique, Waqar Ahmed, Wajih Malik, Hashmat Ullah Khan, Azhar Ijaz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: ischemic heart disease (IHD) remains a leading cause of morbidity and mortality worldwide. Inflammation and oxidative stress are central mechanisms in the development and progression of atherosclerosis. However, their role as clinical predictors of disease severity and outcomes remains underexplored, particularly in South Asian populations. Objective: This study aimed to evaluate the association of serum inflammatory (high-sensitivity C-reactive protein [hs-CRP], interleukin-6 [IL-6]) and oxidative stress biomarkers (malondialdehyde [MDA], superoxide dismutase) with angiographic severity and short-term clinical outcomes in patients with IHD. Methods: A cross-sectional study was conducted at the Punjab Institute of Cardiology, Lahore, between March 2022 and June 2023, including 100 patients with confirmed IHD. Clinical data, echocardiographic findings, and coronary angiographic Gensini scores were recorded. Fasting serum samples were analyzed for hs-CRP, IL-6, MDA, and SOD. Patients were followed for three months for major adverse cardiovascular events (MACE). Results: Higher hs-CRP, IL-6, and MDA levels, and lower SOD activity, were significantly associated with increasing disease severity (p <0.001). Strong correlations were observed between the Gensini score and hs-CRP (r = 0.69), IL-6 (r = 0.73), MDA (r = 0.66), and inverse correlation with SOD (r = –0.61; all p <0.001). Patients who experienced MACE (18%) had significantly higher inflammatory and oxidative biomarkers and lower SOD levels compared to those without events. Conclusion: Serum inflammatory and oxidative biomarkers are robust predictors of angiographic severity and short-term outcomes in IHD. Incorporating these biomarkers into routine risk assessment may improve patient stratification and guide therapeutic strategies. Keywords: ischemic heart disease, hs-CRP, interleukin-6, malondialdehyde, superoxide dismutase, biomarkers, coronary artery disease